A survey of published works in De Computis (2004-2019) - Güvemli, Batuhan; Eskin, İlknur (De Computis, Revista Española de Historia de la Contabilidad., 2021)
This study explores the publishing patterns of a specialized accounting history journal - De Computis, Revista Espanola de Historia de la Contabilidad. The survey is confined to 172 refereed contributions published in 16 years between 2004 and 2019. This article depicts dominant research trends and the decline in research areas by examining authorship patterns, topics, periods, sources, and language. One of our principal findings reveals that the historical research landscape in De Computis is transforming since its inception to Emerging Sources Citation Index in 2015. There is an escalation in non-Spanish articles' percentage and a decline in archival sources' usage. The 18th and 19th centuries stand out as the most popular research periods. We conclude with some suggestions for the journal moving forward.